Pengaruh Model Problem Based Learning Terhadap Kemampuan Berfikir Kreatif dalam Materi Gaya di Sekitar - Eka Nurti Handayani; Feri Faila Sufa; Mukhlis Mustofa (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Abstract. This study aims to determine the significant effect of the Problem Based Learning (PBL) learning model on the creative thinking skills of grade 4 students of Kleco 1 Surakarta Elementary School. This study uses a quantitative approach based on the philosophy of positivism. The population and sample used in this study were 25 grade 4 students of Kleco 1 Surakarta Elementary School. The sampling technique used was purposive sampling. This study used a One-Group Pretest-Posttest Design research design. In this design, before the treatment is given, a pre-test (initial test) is carried out, then treatment is given, and after the treatment is given, a post-test (final test) is carried out. Data collection techniques use observation, testing, and documentation. Based on the results of the study, it can be concluded that the application of the Problem Based Learning (PBL) model has a significant effect on improving the creative thinking skills of grade 4 students of Kleco 1 Surakarta Elementary School in the material of Style Around Us. This is indicated by an increase in the average value from the pretest of 54.4 to 80 in the posttest, as well as the results of the Paired Sample T-test which showed a significant difference before and after treatment.